2012
DOI: 10.5551/jat.13326
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Arterial Stiffness Assessed by Brachial-Ankle Pulse Wave Velocity and Coronary Artery Disease Severity Assessed by the SYNTAX Score

Abstract: Aim:The SYNTAX score is a semi-quantitative angiographic tool used to determine the extent and severity of coronary artery disease (CAD). Automatic computer-assisted measurement of the brachial-ankle pulse wave velocity (baPWV) is a reproducible and valid method by which to assess arterial stiffness. Limited information is available for the association between the SYNTAX score and arterial stiffness in a CAD patient. We aim to assess the association between arterial stiffness determined by PWV and CAD severity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
38
1
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(45 citation statements)
references
References 29 publications
(29 reference statements)
3
38
1
3
Order By: Relevance
“…Obesity is known to be associated with greater arterial stiffness and increased incidence of cardiovascular disease in adulthood. 2,19 Our findings are consistent with the results of previous studies, in which children and adolescents with overweight/obesity presented with higher values of PWV than their peers with normal body weight. 8,9,20 One previous study demonstrated a correlation between PWV and continuous metabolic syndrome score in Indian children.…”
Section: Discussionsupporting
confidence: 92%
“…Obesity is known to be associated with greater arterial stiffness and increased incidence of cardiovascular disease in adulthood. 2,19 Our findings are consistent with the results of previous studies, in which children and adolescents with overweight/obesity presented with higher values of PWV than their peers with normal body weight. 8,9,20 One previous study demonstrated a correlation between PWV and continuous metabolic syndrome score in Indian children.…”
Section: Discussionsupporting
confidence: 92%
“…Therefore, there had been a concern whether baPVW could play a role instead of cfPWV. However, baPWV is easier to perform than cfPWV, therefore it is more commonly used in clinical practice, and its usefulness and prognostic value have been proven in various clinical settings [7][8][9][10][11][12] and meta-analysis [3,13]. In addition, it has been reported that baPWV shows good correlation with cfPWV [42] and aortic stiffness obtained by invasive recording [6].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the brachialankle PWV (baPWV) measurement, which is easy to perform, has become available in clinical practice [6]. Its validity and usefulness were proven in various clinical settings [7][8][9][10][11][12] and meta-analysis [3,13].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, some studies have demonstrated the correlation between arterial stiffness assessed by brachial-ankle pulse wave velocity (baPWV) and the complexity of CAD as evaluated by the SS in CAD patients (11,12). Although arterial stiffness and CAD are closely related, the correlation between arterial stiffness and the complexity of CAD in TAK patients has not been examined.…”
Section: Introductionmentioning
confidence: 99%